Thermal comfort of traditional mud shelters with climate responsive strategies in Nepal - Yonzan, Ankita; Bajracharya, Sushil B. (Kathmandu University Journal of Science Engineering and Technology, 2025)
In Nepal, the vernacular architecture developed with available resources have resulted in traditional buildings being constructed from local materials such as mud, stones, and other organic substances in accordance with climate requirements, as directed by the knowledge and experience of regional builders. Over recent years, urban areas have been rapidly transitioning to modern construction techniques, primarily concrete, causing a reduction in the prevalence of traditional mud shelters, even in rural regions. While traditional mud homes are closely tied to socio-cultural values, tourism, finance, and infrastructure, their ability to deliver thermal comfort has been disregarded over past years due to modern construction practices. To improve the current fragmented studies on thermal comfort, performance, and climate strategies in earthen structures, an interdisciplinary investigation focused on mud structures and their passive strategies for maintaining comfort is conducted. The thermal comfort and thermal performance assessments of mud shelters in the region have shown superior thermal comfort compared to non-mud shelters, with comfort temperatures generally 1-1.5 ° C lower in mud shelters, also confirmed by local inhabitants’ preference. Furthermore, the study proposes improved passive design strategies, including settlement patterns, form, orientation, wall types, openings, and roof and floor conditions, to enhance thermal comfort in mud shelters.